IMPROVING STUDENTS’ VOCABULARY MASTERY IN READING BY USING EXTENSIVE READING AT SMK SINAR HUSNI 2 BM - Agusdiani Purba; Reni Rosianna Lumban Gaol (Journal MELT (Medium for English Language Teaching), 2021)
The aimed of this research was to find out improvement of the students’ vocabulary by Extensive Reading at SMK 2 BM Sinar Husni. This research was a classroom action research. It consisted of two cycles. The procedure research in every cycle consisting of four stage. They planned, act, observed, and contemplating. The subject of research consisted of 30 students from XI SMK Sinar Husni. Post test results in cycle1 there are 8 or 27% of students' who pass through KKM, next to do post test 2 authors give a short story different from cycle1 called "this was fate ". The result of post-test 2 in the second cycle suggests that 26 or 84% pass KKM and that the score is 79,335% of the repairs. This means that the student's vocabulary from the first cycle to the second cycle is successful.